Answer:
12 feet
Step-by-step explanation:
60/6 = 12
Answer:
v = pi(4)^2(16)
2nd choice from top
Step-by-step explanation:
Vary Directly: y = k*x
Vary Inversely: y = k/x
Because x and y vary directly, our equation will look like the first one.
y = k*x
With the inputted values:
-16 = k * 4
Now, to find k, isolate the variable
k = -16/4 = -4
Your final equation will then look like this:
y = -4 * x
Answer:
![1.~e^{-2} \\2.~e^{\frac{7}{2}}\\3.~e^8\\4.~e^{\frac{-11}{2}}](https://tex.z-dn.net/?f=1.~e%5E%7B-2%7D%20%5C%5C2.~e%5E%7B%5Cfrac%7B7%7D%7B2%7D%7D%5C%5C3.~e%5E8%5C%5C4.~e%5E%7B%5Cfrac%7B-11%7D%7B2%7D%7D)
Step-by-step explanation:
We have to simplify the given exponential exponents.
Exponential Properties:
Simplification takes place in the following manner:
a)
![(e^{-3})^\frac{2}{3}\\(e^a)^b = e^{ab}\\=e^{-3\times \frac{2}{3}}\\=e^{-2}](https://tex.z-dn.net/?f=%28e%5E%7B-3%7D%29%5E%5Cfrac%7B2%7D%7B3%7D%5C%5C%28e%5Ea%29%5Eb%20%3D%20e%5E%7Bab%7D%5C%5C%3De%5E%7B-3%5Ctimes%20%5Cfrac%7B2%7D%7B3%7D%7D%5C%5C%3De%5E%7B-2%7D)
b)
![(e^4)(e^{\frac{-1}{2}})\\e^a.e^b = e^{a+b}\\=e^{(4+\frac{-1}{2})} \\= e^{\frac{7}{2}}](https://tex.z-dn.net/?f=%28e%5E4%29%28e%5E%7B%5Cfrac%7B-1%7D%7B2%7D%7D%29%5C%5Ce%5Ea.e%5Eb%20%3D%20e%5E%7Ba%2Bb%7D%5C%5C%3De%5E%7B%284%2B%5Cfrac%7B-1%7D%7B2%7D%29%7D%20%5C%5C%3D%20e%5E%7B%5Cfrac%7B7%7D%7B2%7D%7D)
c)
![(e^{-2})^{-4}\\(e^a)^b = e^{ab}\\= e^{-2\times -4}\\=e^8](https://tex.z-dn.net/?f=%28e%5E%7B-2%7D%29%5E%7B-4%7D%5C%5C%28e%5Ea%29%5Eb%20%3D%20e%5E%7Bab%7D%5C%5C%3D%20e%5E%7B-2%5Ctimes%20-4%7D%5C%5C%3De%5E8)
d)
![(e^{-4})(e^{\frac{-3}{2}})\\e^a.e^b = e^{a+b}\\=e^{(-4+\frac{-3}{2})} \\= e^{\frac{-11}{2}}](https://tex.z-dn.net/?f=%28e%5E%7B-4%7D%29%28e%5E%7B%5Cfrac%7B-3%7D%7B2%7D%7D%29%5C%5Ce%5Ea.e%5Eb%20%3D%20e%5E%7Ba%2Bb%7D%5C%5C%3De%5E%7B%28-4%2B%5Cfrac%7B-3%7D%7B2%7D%29%7D%20%5C%5C%3D%20e%5E%7B%5Cfrac%7B-11%7D%7B2%7D%7D)